PENINGKATAN KEMANDIRIAN ANAK MELALUI KEGIATAN BERMAIN BALOK - Henny Murdhiana; Aulia Ardhana Rizka Nadine; Mustatiroh Nur Rahma Fitriyani; Lesy Ayunda; Ratna Wahyu Pusari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to enhance the independence of children aged 3–4 years through block play activities at the Hj Maryam Kalibeber Nursery School in Wonosobo. The study was motivated by the children’s low level of independence, evident in their behaviour—namely, their continued reliance on teachers’ assistance, lack of self-confidence, and inability to complete tasks independently. The study employed the Classroom Action Research (CAR) method, conducted over two cycles with a sample of 16 children aged 3–4 years. Data collection techniques included observation, interviews, and documentation. The data were analysed using both qualitative and quantitative descriptive methods. The results indicated that block play activities significantly enhanced the children’s independence. In the pre-cycle, 0% of children achieved the ‘Very Good Development’ (VGD) category; this increased to 25% in Cycle I and reached 87.5% in Cycle II. Improvements were observed in children’s ability to make decisions, their self-confidence, sense of responsibility, ability to complete tasks independently, and ability to cooperate with peers. Thus, block play activities are effective as a learning strategy for enhancing social-emotional development, particularly the independence of young children.